Wound Healing Activity of Galam Flower (Melaleuca Cajuputi Subsp. Cumingiana (Turcz.) Barlow) Methanol Extract Wistar Rats - Kartika veranisa putri; Ika Novitasari; Hilma Wardatina; Lilis Tangkeallo; Muhammad Dawud Ashari; Isnaini - Isnaini (Journal of Agromedicine and Medical Sciences, 2022)
Wound is an incontinence condition of skin or mucosal epithelial tissue due to physical or thermal damage. One of the plants that has the potential as a wound healer is gelam (Melaleuca sp). Gelam flower methanol extract has antibacterial activity with a minimum inhibitory level of 1.7 mg/mL. This study aimed to analyze the wound healing activity of gelam flower methanol extract (Melaleuca sp.) in Wistar strain rats that were initiated by the wound seen from the histology of the rat skin. This research uses posttest only method with control group design. Thirty male wistar rats were divided into five groups consisting of a positive control group, a negative control group, 1% gelam flower extract gel, 2% gelam flower extract gel, and 4% gelam flower extract gel. Based on histological data, the positive control treatment group and 4% gel treatment group gave the same results. Both indicate that the skin tissue has begun to connect. The conclusions the three gelam flower methanol extract gel formulas showed wound healing activity and the 4% gelam flower methanol extract gel (Melaleuca Sp.) gave the greatest wound healing activity. Keyword: Melaleuca sp, antibacterial activity, wound initiated healing